Exploring the perspectives of operating room nurses about speaking up in a tertiary hospital in Jordan: A qualitative study - Rania Ali Albsoul; Muhammad Ahmed Alshyyab; Rama M. Nada; Luma Riyad Taweel; Salsabil Awni Flefil; Fatima Abdulsattar Alkubaisi; Majd Alkhawaldeh; Rawan Jamal Mahmoud Harhash; Muna Ali Salameh Ebbini; Hana Taha; James Hughes; Gerard FitzGerald (Journal of Healthcare Risk Management, 2026)
Abstract This study aims to explore operating room nurses' perceptions of speaking up about patient safety issues in a tertiary hospital in Jordan. Speaking up about healthcare errors is a crucial behavior for healthcare providers in their pursuit of maintaining patient safety. A qualitative descriptive design was employed. Semi‐structured individual interviews were conducted between January and March 2024. A total of 12 nurses who were employed in the operating room of a tertiary hospital in Jordan participated in the study. An inductive thematic analysis approach was used to analyze the data. Four main themes were identified from the analysis, namely: “The Power of Nurses' Voice,” “Consequences of Speak up,” “Barriers to speak up,” and “Organizational support for speak up.” The participants identified the culture of hierarchy and heavy workload as barriers that deterred nurses from speaking in the operating room. The findings of this study may guide healthcare managers and decision‐makers to develop interventions to address the cultural and workload issues and thus build a culture where “speaking up” is valued in the operating room context, thus enhancing healthcare quality and patient safety.